Sport Attitudes and Sport Engagement: A Sociological Survey in St. Petersburg in Russia - Sinyutin, Mikhail V.; Gonashvili, Aleksandr S. (Revista da ALESDE, 2023)
The sport policy of Russia over the past decades has resulted in elaboration in 2009 the Strategy for the Development of Sport and Physical Education until 2020 and the State Program “Development of Physical Culture and Sport” from 2014. The key points of these documents are the concern of the population’s health, demographic development and the national security. As a result of the implementation of these programs over the past decade, there has been a significant shift in the engagement of Russians in sport. Therefore, it is interesting to study what are the attitudes and self-esteem of Russian residents towards the sport leisure. In 2021 we conducted the study of St. Petersburg residents in the form of a selective online interview. The study demonstrated that the majority of the residents have positive attitudes towards sport, strong awareness of its importance for the health and for the development of strong-willed personality traits. We also found out that the strong ties of communication are important for St. Petersburg residents to form the sport attitudes, as well as to their willingness to pay for this form of leisure. The study confirmed the key role of free time in the decision of respondents to engage in sport. Comparison of some parameters with similar ones in the countries of the European Union showed similarity in the level of sport engagement with the Scandinavian countries. The results of our study helped us to make conclusions regarding the process of attitudes’ formation of St. Petersburg residents that determine their involvement in sport practices.